Law, Economics and Antitrust Towards a New Perspective - McNutt, Patrick A. (Cheltenham Edward Elgar Pub, 2005)
Using a selection of case studies where appropriate, and examples based in game theory, the book examines these issues from both a law and economics and a microeconomics perspective.
Includes bibliographical references and indexes
uaj 25/02/2015
Loans
Keywords: Law; Economics